Dermomina® clay achieves high closure rates in non-infected diabetic foot ulcers - Camilo Reynoso, Angiolina; Diaz Beltre, Angel; Figueras, Albert (Frontiers in Endocrinology, 2026)
IntroductionDiabetic foot ulcers (DFUs) remain a major global health burden, frequently leading to lower limb amputations, reduced quality of life, and premature mortality. Despite advances in multidisciplinary care, healing outcomes remain suboptimal, particularly in infected ulcers and in low resource settings. There is a need to explore accessible and cost effective adjunctive therapies that may support wound healing and improve outcomes.MethodsA pre experimental observational study was conducted at two wound care units in the Dominican Republic between March 2022 and October 2024. Dermomina clay was applied as a topical adjunct in 24 patients with Wagner grade 1 to 3 diabetic foot ulcers. Patients were stratified according to infection status. Outcomes included time to granulation tissue formation, epithelialization, complete ulcer closure, and safety. Multivariate analysis was performed to explore clinical and wound related factors associated with healing.ResultsFourteen patients presented with non infected ulcers and ten with clinically infected ulcers. Non infected ulcers demonstrated significantly faster healing trajectories and higher closure rates compared with infected ulcers. Median time to complete closure was shorter in the non infected group, and complete closure by week 20 was achieved in 92.9 percent of non infected ulcers compared with 40.0 percent of infected ulcers. Factors associated with delayed healing included age greater than 60 years, HbA1c greater than 7 percent, baseline wound size greater than 20 square centimeters, presence of infection, and higher Wagner grade. Adverse events were infrequent, mild, and transient, with no treatment discontinuations.ConclusionTopical application of Dermomina clay was associated with favorable healing outcomes and a good safety profile, particularly in non infected diabetic foot ulcers. Although causal inference cannot be established, these findings support further evaluation of clay based therapies as low cost adjunctive interventions in diabetic foot care. Larger, controlled trials are warranted to confirm efficacy and define the role of Dermomina within evidence based management strategies for diabetic foot ulcers.